Los estudios áureos de Antonio Alatorre - Carreira, Antonio (El Colegio de México, 2012)
The term “áureos” (“golden”) included in the title should be taken in both senses of the word, indicating the perfection of Alatorre’s own work as wellas the fact that he remained a devoted admirer of the H ispanic GoldenAge throughout his life. Putting to one side his role as an authority onthe work of Sor Juana Inés de la Cruz, and taking into account his activityas a book-reviewer, especially for the NRFH, it is true to say that Alatorrehas bequeathed us an abundance of accomplished studies on outstandingworks and figures such as Garcilaso, Lazarillo de Tormes, Fray Luis de León,Góngora, Juan Ruiz de Alarcón or Quevedo, always with one eye very muchalert to metrical details. An overview of his publications reveals recurrentlines of interest.